Membangun Relasi Ketuhanan Berbasis Tradisi Wiwitan Panen Padi: Studi Etnografi Di Desa Kedungasri Lamongan : Membangun Relasi Ketuhanan Berbasis Tradisi Wiwitan Panen Padi: Studi Etnografi Di Desa Kedungasri Lamongan - Pramudisastra, Abelia; Halim, Abdul (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2025)
This study examines the wiwitan rice harvest tradition in Kedungasri Village, Lamongan, as a form of divine relationship manifested through agrarian cultural practices. The wiwitan tradition is not merely a ritual to welcome the harvest, but also serves as a spiritual medium through which the community expresses gratitude, prayers, and hopes to God for the bounty of the earth. The research employs a qualitative method with an ethnographic approach, involving field observations, interviews, and documentation. The findings reveal that the wiwitan tradition represents harmony between humans, nature, and God, and contains religious, social, and cultural values that are still preserved today, along with rich meanings and symbols. Thus, wiwitan functions not only as a local cultural heritage, but also as a medium to strengthen the village community’s spiritual awareness in building a divine relationship. Keywords: Wiwitan, Divine Relations, Meaning and Symbols, Local Traditions, Ethnography